9x+3=8x+1

Simple and best practice solution for 9x+3=8x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+3=8x+1 equation:


Simplifying
9x + 3 = 8x + 1

Reorder the terms:
3 + 9x = 8x + 1

Reorder the terms:
3 + 9x = 1 + 8x

Solving
3 + 9x = 1 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
3 + 9x + -8x = 1 + 8x + -8x

Combine like terms: 9x + -8x = 1x
3 + 1x = 1 + 8x + -8x

Combine like terms: 8x + -8x = 0
3 + 1x = 1 + 0
3 + 1x = 1

Add '-3' to each side of the equation.
3 + -3 + 1x = 1 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = 1 + -3
1x = 1 + -3

Combine like terms: 1 + -3 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| -4x-(-16)=2x-2 | | 1.92x^2+3.83x+1.92=0 | | F(n)=3+4(n-1) | | 8x-2x+5=-4x+35 | | -4X+39=X+14 | | 6z=2z+24 | | (x-1)+6=8 | | 1.92x^2+3.83t+1.92=0 | | -8x-(-64)=4x+16 | | 3a+4x=12 | | 9+5x=2a+9 | | -13k-5=-k+7 | | -13k-5=-k+7 | | -13k-5=-k+7 | | x^2=784 | | -9x+-45=3x-69 | | F(3)=(-2)n | | 6x-8=3x+4+x | | -8(n+7)=-6(n+4) | | x+(-x-24)=106 | | 29-4x=-7(3x+8) | | 3y=7(y-4) | | 8(2-6x)+19=-61 | | 7(6-2a)=(5-3a+1) | | 9(a+8)=8(a+9)-4 | | -8-(2)= | | 7x(x-3)+4(x-3)= | | (3y+1)(3-y)=0 | | 7x+13+2x-3=55 | | x+(x-24)=106 | | 10e^5x=181 | | 78+.25(78)= |

Equations solver categories